Best Answer

3ab - a - 3b2 + b

= -3b2 + 3ab + b - a

= -3b(b - a) + 1(b - a)

= (1 - 3b)(b - a)

Study guides

☆☆

Q: Factor this expression 3ab-a-3b2 b

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

9a4-b2=36a-2b=2(18-b) But if you meant 9a^4-b^2 it is not possible to factor

2 x 3 x 3 x b x c = 18bc

(2a + 3)(b - 3c)

Use a^3 + b^3 = (a + b)(a^2 - ab + b^2), where a^2 is a squared, a^3 is a cubed. Note that 216 = 6^3.

If the algebraic expression can be written in the form of a(x)/b(x) where a(x) and b(x) are polynomial functions of x and b(x) â‰ 0, then the expression is a rational algebraic expression.

Related questions

a + b + 4 is in its simplest form.

Not sure what the b factor is, but the answer probably is 1, the coefficient of x.

(a - b + 2)(a + b + 2)

(3b - 1)(a - b)

-23

9a4-b2=36a-2b=2(18-b) But if you meant 9a^4-b^2 it is not possible to factor

A linear expression can only have a numeric factor that can be "taken out". The expression will be of the form ax + b where a and b are numbers that have k as their highest common factor (HCF). That is, a = k*c and b = k*d Than being the case, ax + b = kcx + kd = k*(cx + d)

2 x 2 x 2 x 3 x B x C is the expression.

(b + 3)(a + c)

That factors to 4(a - b)(a + 3b)

2 x 3 x 3 x b x c

2 x 3 x 3 x b x c = 18bc

People also asked

Featured Questions